Design of Sports Training Improvement and Evaluation Method under the Background of Big Data. (21st November 2022) - Nie, Baiqi
Abstract : With the development of economic life, the phenomenon of poor health of human beings has gradually appeared, and sports training has also been paid more and more attention. In terms of improving the quality of sports training for students, physical education teachers must first make students aware of the importance of sports training. We should reasonably arrange sports training time, stimulate students' interest and cultivation in sports, improve the results of sports training with scientific and efficient methods, and comprehensively improve the training quality of sports training. Therefore, the following work has been completed in this paper: (1) after searching and sorting out the relevant literature on the improvement and evaluation of sports training methods, this paper constructs a theoretical basis related to this topic. (2) The sports training promotion strategy and evaluation method are proposed, and the basic principles and structure of the DBN model are introduced. (3) We select the optimal parameters of the DBN model through experiments. We input the experimental data collected by big data into the trained model and compare the results with the evaluation results of experts. The experimental results show that the model in this paper has a high accuracy in evaluating the effectiveness of sports training improvement strategies.